Study of epirubicin sustained–release chemoablation in tumor suppression and tumor microenvironment remodeling - Meng, Liangliang; Wang, Zhenjun; Hou, Zhonghui; Wang, Hufei; Zhang, Xiao; Zhang, Xiaobo; He, Xiaofeng; Zhang, Xin; Qin, Boyu; Li, Jing; Zhang, Zhongliang; Xue, Xiaodong; et al. (Frontiers in Immunology, 2022)
Imaging-guided local chemoablation of tumors directly inactivates the tumor cells by antitumor drug injection and preserves the structural integrity of surrounding tissues. Although intratumoral chemoablation can obtain an impressive therapeutic effect, there is still incomplete ablation and tumor recurrence in some patients, and the main reasons for the analysis may include the short retention time of drug in tumors, the limited distribution of intratumoral drugs and beyond that the immunotolerance caused by the tumor microenvironment. So, in this study, we used polyethylene glycol (PEG) hydrogel as a drug carrier to improve the retention time of drugs around the tumor for extending the exposure time of tumor cells to tumoricidal drugs and used epirubicin (EPI) as the main component of chemoablation agent for the immunopotentiation of anthracyclines. We also compared the fluidity of different drug carriers after local injection. In our study, we observed the obvious tumor suppression in tumor volume and inhibition time of tumor growth in the A549 lung cancer mouse model after local injection. And we also observed enhanced antitumor effects of the combination of anti-PD-L1 therapy with local chemoablation for the abscopal tumor reduction in the 4T1 breast model. Flow cytometry analysis of tumor and blood samples showed significant variation of PD-L1+ and CD3+CD8+PD-1+cells between before and after anti-PD-L1 therapy. On the fourth day after local injection of EPI-gel, the expression of PD-L1 in the abscopal tumor is upgraded, and the expression of PD-L1 of bilateral tumors in mice was significantly reduced after anti-PD-L1 treatment. The proportion of CD3+ CD8+ PD-1+ cells in the tumor and circulating blood in the EPI-GEL-PD-L1 group was decreased compared with that in the EPI-GEL group. These results show that the combination of local injection of the chemoablation agent with anti-PD-L1 mAbs may strengthen the antitumor activity and PEG hydrogel as drug carrier of local injection can extend the retention time of chemoablation agent around the tumor, maintaining a long-term tumor-killing activity.